Macrobiotus harmsworthi Murray 1907 ... - Kaczmarek, Łukasz; Michalczyk, Łukasz; Mcinnes, Sandra J. (Zenodo, 2015)
163. Macrobiotus harmsworthi Murray, 1907a sensu lato [T] Makrobiotus harmsworthi Murray? (Richters 1911a) M. harmsworthi Murray (Murray & Wailes 1913) Macrobiotus harmsworthi Murray. (Heinis 1914) Macrobiotus harmsworthi J. Murray 1907 (du Bois-Reymond Marcus 1944, Garitano-Zavala 1995) Macrobiotus harmsworthi J. Murr., 1907 (Ramazzotti 1962a, Ramazzotti 1964a) Macrobiotus harmsworthi J. Murr. (Iharos 1963) M. harmsworthi (Mihelčič 1972, Garitano-Zavala 1996) M. harmsworthi Murray, 1907 (Claps & Rossi 1988) Macrobiotus harmsworthi Murray, 1907 (Maucci 1988, Jerez & Narváez 2001) M. harmsworthi Murray (Claps & Rossi 1997) Macrobiotus cf. harmsworthi (Nickel et al. 2001) Macrobiotus harmsworthi Murray 1907 (Rahm 1931, 1932) Macrobiotus harmsworthi / richtersi (Montoya et al. 2010) Terra typica: Franz Joseph Land (Russia, Barrents Sea) Argentina: • 27°57′S, 58°48′W; 50 m asl: Corrientes Province, Empedrado, Paraje Sombrerito, lichen on power pole (2 samples). Claps & Rossi (1988) • 41°59′S, ... : Published as part of Kaczmarek, Łukasz, Michalczyk, Łukasz & Mcinnes, Sandra J., 2015, Annotated zoogeography of non-marine Tardigrada. Part II: South America, pp. 1-107 in Zootaxa 3923 (1) on pages 66-67, DOI: 10.11646/zootaxa.3923.1.1, http://zenodo.org/record/241936 ...